Peculiarities of some MaxEnt variational treatments using the maximun entropy principle - Plastino, Ángel Luis (2018)
We study some peculiarities of the MaxEnt variational treatment in connection with thermodynamics´ reciprocity relations, which we attack from two view points, an abstract and a straightforward ones. We focus on the so called q-entropy because it illustrates a situation in which the above two approaches yield different results. We detect an information loss in extracting the explicit form of the normalization-associated Lagrange multiplier.